Management of Achievement Development of Pencak Silat Athletes At PRSH College Cilacap Branch - Pangestu, Idi (Media Ilmu Keolahragaan Indonesia, 2024)
Pencak silat PRSH is a martial art sport based on the Setia Hati school. This martial arts has a coach and there are several problems. The problem that can be seen is the management of athlete achievement coaching. The purpose of this study was to determine the management of athlete achievement coaching. The subjects in this study were administrators, coaches, and athletes. Data collection used through observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and conclusion drawing. Based on the results obtained that, 1) the first stage, namely athlete massaging, as a whole has not gone well because athletes do not know the actual vision, mission and goals, and lack of infrastructure to support training, 2) the second stage, namely athlete breeding, in this case the implementation has not gone well and can be seen from the recruitment of athletes who still do not have specific criteria, 3) the third stage, namely achievement results, is also still not going well, coordination and provision of information from administrators and coaches only through WhatsApp and Instagram groups, training programs are carried out only 3 months before the match so that the results of athlete development have not increased significantly. The conclusion from the results of this study is that the management of athlete achievement coaching is still not going well enough. The suggestion of this researcher is that the management of coaching athlete achievement still needs improvement, especially in training programs.